Models of “sustainable agriculture” with special emphasis on the wine sector - Cristiani, Eloisa (Przegląd Prawa Rolnego, 2018)
In 2015, the UN adopted 2030 Agenda for Sustainable Development, which includes Goal 2, on the promotion of sustainable agriculture. The EU’s “Europe 2020” strategy and the Communication on “The CAP towards 2020” aim at building a “more sustainable, smarter and more inclusive growth for rural Europe.” This new model of growth emphasises the key role of agriculture within climate change adaptation, as has also been emphasised at COP 22. Indeed, agriculture is responsible for almost 20% of GHG emissions, and should thus contribute to climate change mitigation, and climate resilience. But, what kind of agriculture do we refer to? Is there a common and univocal notion of sustainable agriculture? Are green practices able to reduce global C02 emissions? Are sustainable agriculture and the “precision agriculture “connected? The wine sector, where there are more than 15 different models of procedural guidelines, protocols etc. referring to the notion of sustainability is an ideal case study.